2013
DOI: 10.6004/jnccn.2013.0147
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Routine Screening for Distress, the Sixth Vital Sign, for Patients With Head and Neck and Neurologic Cancers

Abstract: This study examined the benefits of incorporating screening for distress as a routine part of care for patients with head and neck and neurologic cancers in a tertiary cancer center. Using a comparative 2-cohort pre-post implementation sequential design, consecutive outpatients with head and neck and neurologic cancers were recruited into 2 separate cohorts. Cohort 1 included patients attending clinics during April 2010, before the implementation of the screening program. The program was then implemented and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…[4][5][6][7][8] It is widely acknowledged that successful implementation of screening programs depends on health professionals' knowledge and skills 9,10 ; however, health professionals themselves have reported a perceived lack of skills in identifying distress and a lack of guidance around referral pathways. 12 In a recent implementation study of routine screenings for distress in the clinical environment using existing staff, 13 we used a quality improvement methodology to address challenges in following screening protocols, which involved continually identifying and addressing areas in which process change was required. 12 In a recent implementation study of routine screenings for distress in the clinical environment using existing staff, 13 we used a quality improvement methodology to address challenges in following screening protocols, which involved continually identifying and addressing areas in which process change was required.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] It is widely acknowledged that successful implementation of screening programs depends on health professionals' knowledge and skills 9,10 ; however, health professionals themselves have reported a perceived lack of skills in identifying distress and a lack of guidance around referral pathways. 12 In a recent implementation study of routine screenings for distress in the clinical environment using existing staff, 13 we used a quality improvement methodology to address challenges in following screening protocols, which involved continually identifying and addressing areas in which process change was required. 12 In a recent implementation study of routine screenings for distress in the clinical environment using existing staff, 13 we used a quality improvement methodology to address challenges in following screening protocols, which involved continually identifying and addressing areas in which process change was required.…”
mentioning
confidence: 99%
“…Ten studies were conducted in the UK (Biddle et al, ; Dennison & Shute, ; Ferguson & Aning, ; Fulcher & Gosselin‐Acomb, ; Ghazali et al, ; Hollingworth et al, ; Ipsos Mori, ; Lee, Katona, Bono, & Lewis, ; Mitchell, Lord, Slattery, Grainger, & Symonds, ; Rogers & Lowe, ). Five were conducted in Canada (Carlson, Groff, Maciejewski, & Bultz, ; Carlson, Waller, Groff, & Bultz, ; Carlson et al, ; Fillion et al, ; Bultz et al, ), two in Australia (Ristevski et al, ; Thewes, Butow, & Stuart‐Harris, ) and three in Europe (Dolbeault, Boistard, Meuric, Copel, & Brédart, ; Lynch, Goodhart, Saunders, & O'Connor, ; Thayssen et al, ). Although most studies involved patients with a range of cancer types, three focussed only on patients with head and neck cancer (Bultz et al, ; Ghazali et al, ; Rogers & Lowe, ) and two exclusively on lung cancer (Carlson et al, ; Lynch et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported the results of a randomised controlled trial (RCT) (Carlson et al, , ; Carlson, Waller, Groff, Zhong, & Bultz, ; Hollingworth et al, ). A further eight evaluations (Bultz et al, ; Dolbeault et al, ; Ferguson & Aning, ; Fulcher & Gosselin‐Acomb, ; Ghazali et al, ; Ipsos Mori, ; Lee et al, ; Rogers & Lowe, ) presented findings from research or evaluation that aimed to quantify or qualify changes in patient and/or practice outcomes as a result of the HNA. The remaining eight studies reported on work to determine the feasibility or acceptability to practitioners and/or patients of implementing some form of HNA (Biddle et al, ; Dennison & Shute, ; Fillion et al, ; Lynch et al, ; Mitchell et al, ; Ristevski et al, ; Thayssen et al, ; Thewes et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Initial findings indicated benefits in terms of greater efficiency, rapid identification of key patient concerns, a decrease in patient encounters with the clinic, improvement in patient self‐reports of well‐being and quality of life. From the frontline staff, there was an expression of increased confidence that the clinic was providing comprehensive care to its patients and an increase in comfort with screening …”
Section: Lessons Learnedmentioning
confidence: 99%